Estudo dos processos referenciais em textos do colunista José Simão - Silva, Ana Paula da (2014)
The primary objective of this research is to analyze the use of referential processes in the texts of the columnist from Folha de S. Paulo journal José Simão. Therefore, the objective is to find what is the function of each one of these elements used by the author, and its implications for the interpretation in the use of this processes. To reach this, the study was based on the functionalist assumptions and textual linguistics. The first perspective aims to study the linguistics expressions related to the communicative purposes of the speaker and to contribute to evidence the used language, in its different ways of manifestations. The second perspective deals with referential processes in texts - another form of interaction. Both converge to the fact that consider the communicative event - oral and/or written - as a form of dialogue. The corpus of this study consists by 10 texts of columnist Zé Simão, published daily in the illustrated section of the Folha de S. Paulo, for the period of one year (from March, 9 of 2.013 until March, 8 of 2.014). The extension of texts followed by the number of kbytes (the texts chosen were those with 17 kbytes) for the amount of change processes found not suffer due to the extension of each text. The work follows the methodology of the empirical-inductive line, which formulates judgments through observation of facts and experiences, from the characteristics of the corpus in question. The survey results showed that the most recurrent cases were: indirect anaphora (191 occurrences), the catáfora (97 occurrences), repetition (71 occurrences) and the lettering (47 occurrences). In this research universe indirect anaphora pointed out the need for the reader to be able to make inferences on various extralinguistic instances - specific, surface and bottom. Highlighted the significant number of catáforas related to prospective lettering and repetition as a mnemonic strategy that is consolidated in the collective memory of the reader. Thus, the different jobs these references processes establish a close relationship with nature and the motivation of natural speech columnist acquiring proper signification.